Giving or Receiving Gifts? Reexamining Paul's Use of Psalm 68:18 in Ephesians 4:8 - Fields, C. Ryan (The Evangelical quarterly, 2021)
The severity of difficulties surrounding Paul's use of Psalm 68:18 in Ephesians 4:8 is well known. I argue that Ephesians 4:8 is best understood as an instance of Paul quoting Psalm 68:18 against a broader canonical backdrop, putting the themes of Psalm 68 in dialogue with other portions of the ot (especially Numbers 8) while engaging in typological and christological reflection on the nature of the church as a diversely gifted community. I make this argument by evaluating seven major interpretive options for understanding Paul's use of the ot here. I then assess the two most promising options by examining Psalm 68 in its relation to Judges 5 and Numbers 8 and by investigating the extent to which these canonical co-texts might have informed Paul's appropriation of the psalm, concluding that more attention should be given to the possibility that Paul is engaged in a christological reading of Numbers 8.